Preparation method of nano silicon dioxide modified polyurethane thermal insulation material
By adding benzoxazine-based bisnano silica and benzoxazine-based bis-PEPA to the polyurethane insulation material, an organic-inorganic flame retardant system is formed, which solves the problem of flammability of polyurethane insulation materials and improves the flame retardant, antibacterial, mechanical and thermal stability properties of the material.
Patent Information
- Application Number
- CN202510135926.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polyurethane insulation materials are flammable and have poor fire resistance, which limits their application areas.
By adding benzoxazine-based bisnano silica and benzoxazine-based bisPEPA to the polyurethane material, the organic-inorganic flame retardant system is formed by using its thermal stability and antibacterial properties to improve the flame retardant, antibacterial, mechanical and thermal stability properties of the material.
The prepared nano-silica modified polyurethane insulation material has good antibacterial properties, flame retardant properties, mechanical properties and thermal stability, which expands its application potential in construction engineering and other fields.
Smart Images

Figure CN119842038A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane thermal insulation materials, in particular to a method for preparing a nano-silicon dioxide modified polyurethane thermal insulation material. Background Art
[0002] Polyurethane thermal insulation material is an important type of thermal insulation material, which is widely used in fields such as construction engineering. However, polyurethane thermal insulation material is extremely flammable and has poor fire resistance, which limits its application in many fields. Therefore, preparing a polyurethane thermal insulation material with flame retardant effect is one of the important research directions to expand its application field.
[0003] Nano-silica is an important inorganic material, commonly known as white carbon black. Because it is an ultrafine nano-based material, it has many excellent and unique properties, such as being able to improve the material's anti-aging, strength and chemical resistance. It is widely used in catalysis, light filtering, light absorption, medicine, new materials and other fields. 1-Oxophospha-4-hydroxymethyl-2,6,7-trioxabicyclo[2,2,2]octane (PEPA) is favored by researchers because of its highly symmetrical cage structure, good carbonization, excellent thermal stability, and rich carbon and acid sources.
[0004] For example, the patent with authorization announcement number CN114106683B discloses a waterproof and thermal insulation integrated material and its production process. The invention uses polyurethane materials, nano-silicon dioxide, etc. as raw materials. The prepared material has good flame retardant effect and mechanical properties, but does not improve the antibacterial properties and thermal stability of the material. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing a nano-silicon dioxide modified polyurethane thermal insulation material. The prepared thermal insulation material has good antibacterial properties, flame retardancy, mechanical properties and thermal stability.
[0007] (II) Technical solution
[0008] A preparation method of a nano-silicon dioxide modified polyurethane thermal insulation material, the preparation method comprising:
[0009] The polyether polyol, foam stabilizer, catalyst, foaming agent and deionized water are stirred for 5-10 minutes to be evenly mixed, and then benzoxazine-based double nano-silica and benzoxazine-based double PEPA are added thereto and stirred to be evenly mixed, and then a curing agent is added thereto, and the mixture is stirred at a speed of 3000 rpm for 10-20 seconds, and then the mixture is quickly poured into a mold of 300 mm×300 mm×150 mm, and foamed and molded, and the mold temperature is controlled at 50° C. to obtain a nano-silica modified polyurethane thermal insulation material.
[0010] Preferably, the mass ratio of the polyether polyol, foam stabilizer, catalyst, foaming agent, deionized water, benzoxazine-based double nano-silica, benzoxazine-based bis-PEPA, and curing agent is 80-100:1-2:1-2:20-25:1-2:5-20:1-10:100.
[0011] Preferably, the catalyst is one of N,N-dimethylcyclohexylamine and dibutyltin dilaurate.
[0012] Preferably, the preparation method of the benzoxazinyl bis-PEPA is:
[0013] (1) Add 4-chloro-1-butylamine and formaldehyde to a dioxane solvent, stir at room temperature for 30-40 minutes, then add bisphenol A, heat to 80-90° C., react for 8-12 hours, and after the reaction is completed, cool to room temperature, rotary evaporate, and dry to obtain intermediate 1;
[0014] (2) PEPA is added to acetonitrile solvent, stirred and dispersed, heated to 55-65° C., intermediate 1 is added thereto, stirred and mixed evenly, heated to 85-90° C., pyridine is added thereto, refluxed for 22-26 hours, and after the reaction is completed, filtered while hot, washed with ethanol, and dried to obtain benzoxazinyl bis-PEPA.
[0015] More preferably, in (1), the molar ratio of 4-chloro-1-butylamine, formaldehyde and bisphenol A is 2-2.5:6-7:1.
[0016] More preferably, in (2), the molar ratio of PEPA, intermediate 1, and pyridine is 2-2.5:1:0.4-0.6.
[0017] Furthermore, the preparation method of the benzoxazine-based double nano-silica is:
[0018] S1. Under nitrogen protection, add N,N-diethyl-aminopropylmethyldimethoxysilane to ethanol solvent, stir and disperse, add the intermediate 1 at 50-55°C, react for 8-12h, and after the reaction, cool to room temperature, rotary evaporate, wash with ether, and dry to obtain intermediate 2;
[0019] S2. Add intermediate 2 to toluene solvent, stir and disperse, then add nano-silica, continue stirring for 20-40 minutes, add 75% by mass ethanol aqueous solution, heat and reflux for 2-3 hours, after completion, cool to room temperature, filter, wash with toluene and ether in turn, and dry to obtain benzoxazine-based double nano-silica.
[0020] Further preferably, in S1, the molar ratio of N,N-diethyl-aminopropylmethyldimethoxysilane to intermediate 1 is 2-2.4:1.
[0021] Further preferably, in S2, the mass ratio of the intermediate 2 to the nano-silicon dioxide is 4-6:1.
[0022] (III) Beneficial technical effects
[0023] The invention obtains benzoxazine-based double nano-silica and benzoxazine-based double PEPA through a series of reactions. The preparation method is simple and the structure is novel. The benzoxazine-based double nano-silica and benzoxazine-based double PEPA are added to a polyurethane thermal insulation material, and the property of the benzoxazine structure contained therein being easy to open and cross-link when heated is utilized to synergistically improve the thermal stability of the polyurethane thermal insulation material with inorganic heat-resistant nano-silica and heat-resistant benzene ring structure; the property of the double quaternary ammonium salt structure therein having an antibacterial effect is utilized to introduce it into the polyurethane thermal insulation material to improve the antibacterial property of the material; the phosphorus-containing group therein is utilized to generate highly dehydrating polyphosphoric acid during the combustion process, so that the material is rapidly dehydrated and carbonized, and the polyphosphoric acid is covered on the surface of the material, so that oxygen diffusion to the reaction zone is inhibited, and the production of combustible gas is inhibited, and an organic-inorganic flame retardant system is formed with the inorganic nano-silica to synergistically improve the flame retardant property of the material. In addition, the benzoxazine-based double nano-silica and benzoxazine-based double PEPA prepared by the present invention not only contain nano-silica as a stress concentration point with good dispersibility, but also have more long-chain structures, which can be entangled with each other to form more cross-linking sites, and the two assist each other to synergistically improve the mechanical properties of the material. The polyurethane thermal insulation material prepared by the present invention has good antibacterial properties, flame retardant properties, mechanical properties and thermal stability properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the reaction route of intermediate 1;
[0025] Figure 2 This is the reaction route of intermediate 2;
[0026] Figure 3 This is the reaction route for benzoxazinyl bis-PEPA. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] (1) 0.2 mol of 4-chloro-1-butylamine and 0.65 mol of formaldehyde were added to a dioxane solvent, stirred at room temperature for 40 min, and then 0.1 mol of bisphenol A was added thereto. The temperature was raised to 85° C. and the reaction was carried out for 10 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, and dried to obtain intermediate 1.
[0030] (2) 1 mol of PEPA was added to acetonitrile solvent, stirred and dispersed, heated to 60°C, 0.5 mol of intermediate 1 was added thereto, stirred and mixed evenly, heated to 90°C, 0.25 mol of pyridine was added thereto, refluxed for 25 hours, and after the reaction was completed, filtered while hot, washed with ethanol, and dried to obtain benzoxazinyl bis-PEPA.
[0031] (3) Under nitrogen protection, 1 mol of N,N-diethyl-aminopropylmethyldimethoxysilane was added to an ethanol solvent and stirred for dispersion. At 55° C., 0.5 mol of intermediate 1 was added thereto and reacted for 10 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, washed with ether, and dried to obtain intermediate 2.
[0032] (4) Add 40 g of intermediate 2 to toluene solvent, stir and disperse, then add 10 g of nano-silica, continue stirring for 30 min, add 75% by mass ethanol aqueous solution, heat and reflux for 2 h, and after cooling to room temperature, filter, wash with toluene and ether in turn, and dry to obtain benzoxazine-based double nano-silica.
[0033] (5) 80 g of polyether polyol (LY-4110), 2 g of foam stabilizer (AK8814), 1 g of N,N-dimethylcyclohexylamine catalyst, 25 g of hydrofluorocarbon foaming agent (HFC-365mfc), and 1 g of deionized water were stirred for 8 min to mix evenly, and then 5 g of benzoxazine-based double nano-silica and 1 g of benzoxazine-based double PEPA were added thereto to mix evenly, and then 100 g of polyphenyl polymethylene polyisocyanate (PM-200) curing agent was added thereto, stirred at a speed of 3000 rpm for 20 s, and then quickly poured into a 300 mm × 300 mm × 150 mm mold, foamed and molded, and the mold temperature was controlled at 50 ° C to obtain a nano-silica modified polyurethane thermal insulation material.
[0034] Example 2
[0035] (1) 0.25 mol of 4-chloro-1-butylamine and 0.6 mol of formaldehyde were added to a dioxane solvent, stirred at room temperature for 40 min, and then 0.1 mol of bisphenol A was added thereto. The temperature was raised to 90° C. and the reaction was carried out for 8 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, and dried to obtain intermediate 1.
[0036] (2) 1.2 mol of PEPA was added to acetonitrile solvent, stirred and dispersed, heated to 65° C., 0.5 mol of intermediate 1 was added thereto, stirred and mixed evenly, heated to 90° C., 0.25 mol of pyridine was added thereto, refluxed for 24 h, and after the reaction was completed, filtered while hot, washed with ethanol, and dried to obtain benzoxazinyl bis-PEPA.
[0037] (3) Under nitrogen protection, 1.2 mol of N,N-diethyl-aminopropylmethyldimethoxysilane was added to an ethanol solvent and stirred for dispersion. At 55°C, 0.5 mol of intermediate 1 was added thereto and reacted for 8 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, washed with ether, and dried to obtain intermediate 2.
[0038] (4) Add 45 g of intermediate 2 to toluene solvent, stir and disperse, then add 10 g of nano-silica, continue stirring for 20 min, add 75% by mass ethanol aqueous solution, heat and reflux for 2 h, and after cooling to room temperature, filter, wash with toluene and ether in turn, and dry to obtain benzoxazine-based double nano-silica.
[0039] (5) 90 g of polyether polyol (LY-4110), 2 g of foam stabilizer (AK8814), 1 g of dibutyltin dilauric acid catalyst, 20 g of hydrofluorocarbon foaming agent (HFC-365mfc), and 2 g of deionized water were stirred for 5 min to mix evenly, and then 10 g of benzoxazine-based double nano-silica and 3 g of benzoxazine-based double PEPA were added thereto to mix evenly, and then 100 g of polyphenyl polymethylene polyisocyanate (PM-200) curing agent was added thereto, stirred at a speed of 3000 rpm for 15 s, and then quickly poured into a 300 mm × 300 mm × 150 mm mold, foamed and molded, and the mold temperature was controlled at 50 ° C to obtain a nano-silica modified polyurethane thermal insulation material.
[0040] Example 3
[0041] (1) 0.24 mol of 4-chloro-1-butylamine and 0.7 mol of formaldehyde were added to a dioxane solvent, stirred at room temperature for 30 min, and then 0.1 mol of bisphenol A was added thereto. The temperature was raised to 80° C. and the reaction was carried out for 12 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, and dried to obtain intermediate 1.
[0042] (2) 1 mol of PEPA was added to acetonitrile solvent, stirred and dispersed, heated to 60°C, 0.5 mol of intermediate 1 was added thereto, stirred and mixed evenly, heated to 90°C, 0.2 mol of pyridine was added thereto, and refluxed for 22 hours. After the reaction was completed, the mixture was filtered while hot, washed with ethanol, and dried to obtain benzoxazinyl bis-PEPA.
[0043] (3) Under nitrogen protection, 1.2 mol of N,N-diethyl-aminopropylmethyldimethoxysilane was added to an ethanol solvent and stirred for dispersion. At 50°C, 0.5 mol of intermediate 1 was added thereto and reacted for 12 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, washed with ether, and dried to obtain intermediate 2.
[0044] (4) Add 50 g of intermediate 2 to toluene solvent, stir and disperse, then add 10 g of nano-silica, continue stirring for 30 min, add 75% by mass ethanol aqueous solution, heat and reflux for 2 h, and after cooling to room temperature, filter, wash with toluene and ether in turn, and dry to obtain benzoxazine-based double nano-silica.
[0045] (5) 100 g of polyether polyol (LY-4110), 1 g of foam stabilizer (AK8814), 2 g of dibutyltin dilauric acid catalyst, 22 g of hydrofluorocarbon foaming agent (HFC-365mfc), and 1 g of deionized water were stirred for 5 min to mix evenly, and then 15 g of benzoxazine-based double nano-silica and 6 g of benzoxazine-based double PEPA were added thereto to mix evenly, and then 100 g of polyphenyl polymethylene polyisocyanate (PM-200) curing agent was added thereto, stirred at a speed of 3000 rpm for 10 s, and then quickly poured into a 300 mm × 300 mm × 150 mm mold, foamed and molded, and the mold temperature was controlled at 50 ° C to obtain a nano-silica modified polyurethane thermal insulation material.
[0046] Example 4
[0047] (1) 0.2 mol of 4-chloro-1-butylamine and 0.65 mol of formaldehyde were added to a dioxane solvent, stirred at room temperature for 35 min, and then 0.1 mol of bisphenol A was added thereto. The temperature was raised to 90° C. and the reaction was carried out for 8 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, and dried to obtain intermediate 1.
[0048] (2) 1.25 mol of PEPA was added to acetonitrile solvent, stirred and dispersed, heated to 55° C., 0.5 mol of intermediate 1 was added thereto, stirred and mixed evenly, heated to 90° C., 0.3 mol of pyridine was added thereto, and refluxed for 26 hours. After the reaction was completed, the mixture was filtered while hot, washed with ethanol, and dried to obtain benzoxazinyl bis-PEPA.
[0049] (3) Under nitrogen protection, 1.2 mol of N,N-diethyl-aminopropylmethyldimethoxysilane was added to an ethanol solvent and dispersed with stirring. At 55° C., 0.5 mol of intermediate 1 was added thereto and reacted for 10 h. After the reaction was completed, the mixture was cooled to room temperature, rotary evaporated, washed with ether, and dried to obtain intermediate 2.
[0050] (4) Add 60 g of intermediate 2 to toluene solvent, stir and disperse, then add 10 g of nano-silica, continue stirring for 40 min, add 75% by mass ethanol aqueous solution, heat and reflux for 3 h, cool to room temperature, filter, wash with toluene and ether in turn, and dry to obtain benzoxazine-based double nano-silica.
[0051] (5) 95 g of polyether polyol (LY-4110), 1 g of foam stabilizer (AK8814), 2 g of N,N-dimethylcyclohexylamine catalyst, 22 g of hydrofluorocarbon foaming agent (HFC-365mfc), and 1 g of deionized water were stirred for 10 min to mix evenly, and then 20 g of benzoxazine-based double nano-silica and 10 g of benzoxazine-based double PEPA were added thereto to mix evenly, and then 100 g of polyphenyl polymethylene polyisocyanate (PM-200) curing agent was added thereto, stirred at a speed of 3000 rpm for 15 s, and then quickly poured into a 300 mm × 300 mm × 150 mm mold for foaming molding, and the mold temperature was controlled at 50 ° C to obtain a nano-silica modified polyurethane thermal insulation material.
[0052] Comparative Example 1
[0053] The difference between this comparative example and Example 1 is that nano-silica is used in step (5) instead of benzoxazine-based double nano-silica.
[0054] Comparative Example 2
[0055] The difference between this comparative example and Example 1 is that step (5) does not contain benzoxazinyl bis-PEPA.
[0056] Flame retardant performance test:
[0057] Use an oxygen index tester to perform oxygen index testing.
[0058] UL-94 rating is tested using a horizontal vertical burning apparatus.
[0059] Table 1:
[0060] Oxygen index (%) UL-94 Rating Example 1 27.9 V-0 Example 2 29.4 V-0 Example 3 31.3 V-0 Example 4 32.2 V-0 Comparative Example 1 27.0 V-0 Comparative Example 2 24.2 V-1
[0061] It can be seen from the table that the flame retardant effect of Examples 1-4 is better than that of Comparative Examples 1-2. This is because benzoxazinyl double nano-silica and benzoxazinyl bis-PEPA structures are added to Examples 1-4. It can be seen from Examples 1-4 that as the amount of benzoxazinyl double nano-silica and benzoxazinyl bis-PEPA increases, the flame retardant effect becomes better. It can be seen from Comparative Example 1 and Example 1 that the difference between the two is that Comparative Example 1 uses nano-silica and Example 1 uses benzoxazinyl double nano-silica. The flame retardant effect of Example 1 is better than that of Comparative Example 1. This is because nano-silica itself is easy to agglomerate, and the modified nano-silica can be evenly dispersed in the material matrix, and the larger specific surface area and smaller particle size can better play a heat insulation and oxygen isolation effect. Therefore, the effect of Example 1 is better than that of Comparative Example 1.
[0062] Antibacterial performance test:
[0063] (1) The polyurethane thermal insulation material was cut into 1 cm × 1 cm pieces, washed with ethanol, and dried.
[0064] (2) Activate E. coli and prepare a bacterial suspension of 1×104 cfu / ml to 5×104 cfu / ml. Place the cut sample into a conical flask containing the bacterial suspension, fix it on a shaking table, shake it at 25°C and 300 r / min for 5 min, and take 1 mL of the bacterial suspension for 100-fold dilution.
[0065] (3) 1 mL of the bacterial suspension was inoculated into an agar dish and cultured at 37°C under natural light for 48 h. The colonies were counted according to the method in GB15979-2003.
[0066] Bacterial inhibition rate (%) = (average colony count before sample shaking - average colony count after sample shaking) / average colony count before sample shaking × 100%.
[0067] Table 2:
[0068] Antibacterial rate (%) Example 1 85.6 Example 2 92.3 Example 3 98.4 Example 4 99.9 Comparative Example 1 -
[0069] As can be seen from the table, the thermal insulation material prepared by the present invention has a good antibacterial effect, and the antibacterial rate can reach up to 99.9%. This is because Examples 1-4 contain benzoxazine-based double nano-silica, which contains a gemini quaternary ammonium salt structure, which has a good antibacterial effect. Therefore, the antibacterial effect of Examples 1-4 is better than that of Comparative Example 1.
[0070] Thermal stability test:
[0071] The thermal stability of the material was tested using a thermogravimetric analyzer with a sample mass of 10 mg. The gas flow rate was 20 mL / min, the heating rate was 10 °C / min, and the temperature range was 40-800 °C under a nitrogen atmosphere.
[0072] Table 3:
[0073]
[0074]
[0075] As can be seen from the table, the thermal insulation material prepared by the present invention has good thermal stability. The thermal stability of Examples 1-4 is greater than that of Comparative Examples 1-2. This is because Examples 1-4 contain benzoxazinyl double nano-silica and benzoxazinyl double PEPA structure, and as the amount of the two increases, the thermal stability increases. The difference between Example 1 and Comparative Example 1 is that Example 1 adds benzoxazinyl double nano-silica, and Comparative Example 1 uses nano-silica instead of benzoxazinyl double nano-silica. In Example 1, there is a benzoxazine structure with good thermal stability, but there is no benzoxazine structure in Comparative Example 1, so its effect is poor. The difference between Comparative Example 2 and Example 1 is that it does not contain a benzoxazinyl double PEPA structure, so the effect of Comparative Example 2 is not as good as that of Example 1. Therefore, the thermal insulation material prepared by the present invention has good thermal stability.
[0076] Mechanical properties test: Refer to GB / T6344-2008 to test the tensile strength of materials.
[0077] Table 4:
[0078] Tensile strength / kPa Example 1 135 Example 2 148 Example 3 160 Example 4 164 Comparative Example 1 118 Comparative Example 2 129
[0079] As can be seen from the table, the thermal insulation material prepared by the present invention has good mechanical properties. It can be seen from Examples 1-4 that with the increase in the amount of benzoxazine-based double nano-silica and benzoxazine-based bis-PEPA structure, the tensile strength is also increasing. The test result of Comparative Example 2 is better than that of Comparative Example 1. This is because the modified nano-silica can be evenly dispersed in the material matrix, while Comparative Example 1 is unmodified nano-silica, which is easy to agglomerate in the matrix, so its mechanical properties are not as good as those of Comparative Example 2.
Claims
1. A method for preparing a nano-silicon dioxide modified polyurethane thermal insulation material, characterized in that: The preparation method is: The polyether polyol, foam stabilizer, catalyst, foaming agent and deionized water are stirred for 5-10 minutes to be evenly mixed, and then benzoxazine-based double nano-silica and benzoxazine-based double PEPA are added thereto and stirred to be evenly mixed, and then a curing agent is added thereto, and the mixture is stirred at a speed of 3000 rpm for 10-20 seconds, and then the mixture is quickly poured into a mold of 300 mm×300 mm×150 mm, and foamed and molded, and the mold temperature is controlled at 50° C. to obtain a nano-silica modified polyurethane thermal insulation material.
2. The method for preparing the nano-silicon dioxide modified polyurethane thermal insulation material according to claim 1, characterized in that: The mass ratio of the polyether polyol, foam stabilizer, catalyst, foaming agent, deionized water, benzoxazine-based double nano-silica, benzoxazine-based double PEPA, and curing agent is 80-100:1-2:1-2:20-25:1-2:5-20:1-10:
100.
3. The method for preparing the nano-silicon dioxide modified polyurethane thermal insulation material according to claim 1, characterized in that: The catalyst is one of N,N-dimethylcyclohexylamine and dibutyltin dilaurate.
4. The method for preparing the nano-silicon dioxide modified polyurethane thermal insulation material according to claim 1, characterized in that: The preparation method of the benzoxazinyl bis-PEPA is as follows: (1) Add 4-chloro-1-butylamine and formaldehyde to a dioxane solvent, stir at room temperature for 30-40 minutes, then add bisphenol A, heat to 80-90° C., react for 8-12 hours, and after the reaction is completed, cool to room temperature, rotary evaporate, and dry to obtain intermediate 1; (2) PEPA is added to acetonitrile solvent, stirred and dispersed, heated to 55-65° C., intermediate 1 is added thereto, stirred and mixed evenly, heated to 85-90° C., pyridine is added thereto, refluxed for 22-26 hours, and after the reaction is completed, filtered while hot, washed with ethanol, and dried to obtain benzoxazinyl bis-PEPA.
5. The method for preparing the nano-silicon dioxide modified polyurethane thermal insulation material according to claim 4, characterized in that: In the above (1), the molar ratio of 4-chloro-1-butylamine, formaldehyde and bisphenol A is 2-2.5:6-7:
1.
6. The method for preparing the nano-silicon dioxide modified polyurethane thermal insulation material according to claim 4, characterized in that: In the above (2), the molar ratio of PEPA, intermediate 1 and pyridine is 2-2.5:1:0.4-0.
6.
7. The method for preparing the nano-silicon dioxide modified polyurethane thermal insulation material according to claim 1, characterized in that: The preparation method of the benzoxazine-based double nano-silica is as follows: S1. Under nitrogen protection, add N,N-diethyl-aminopropylmethyldimethoxysilane to ethanol solvent, stir and disperse, add the intermediate 1 at 50-55°C, react for 8-12h, and after the reaction, cool to room temperature, rotary evaporate, wash with ether, and dry to obtain intermediate 2; S2. Add intermediate 2 to toluene solvent, stir and disperse, then add nano-silica, continue stirring for 20-40 minutes, add 75% by mass ethanol aqueous solution, heat and reflux for 2-3 hours, after completion, cool to room temperature, filter, wash with toluene and ether in turn, and dry to obtain benzoxazine-based double nano-silica.
8. The method for preparing the nano-silicon dioxide modified polyurethane thermal insulation material according to claim 7, characterized in that: In the S1, the molar ratio of N,N-diethyl-aminopropylmethyldimethoxysilane to the intermediate 1 is 2-2.4:
1.
9. The method for preparing the nano-silicon dioxide modified polyurethane thermal insulation material according to claim 7, characterized in that: In the S2, the mass ratio of the intermediate 2 to the nano-silicon dioxide is 4-6:1.
Citation Information
Patent Citations
A waterproof and thermal insulation integrated material and its production process
CN114106683B
Preparation method of benzoxazine intermediate containing active function groups
CN101041644A
Polybenzoxazine / mesoporous molecular sieve hybrid material and preparation method thereof
CN101921477A
Homogeneous suspension of immunopotentiating compounds and uses thereof
CN102762206A
DOPO-containing bisphenol A-monobenzoxazine / epoxy resin copolymer and preparation method thereof
CN104193967A
Cited By
Thermal insulation material and finished product crystallization reaction kettle applied to intermediate synthesis
CN121537598A